Effects of Early Morning Exercise on Serum Brain-Derived Neurotrophic Factor Level and Its Relation With Blood Cholesterol and Glucose Levels in the Elderly Men - Vahid Valipour Dehnouhnou; Mehdi Abbasi Moghadam; Mohammad Soleymani Farsani (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives Early morning exercise is prevalent in Iranian population, and yet no study has assessed its effect on brain-derived neurotrophic factor. Therefore, the purpose of this study was to assess the effect of early morning exercise on serum levels of brain-derived neurotrophic factor and its relation with cholesterol levels in the elderly males in Khorramabad City, Iran. Methods & Materials In this quasi-experimental study, 13 older men (mean [SD] age: 56.46[3.93] y; mean [SD] weight 82.46[8.23] kg; mean [SD] height: 175.46[5.17] cm) voluntarily participated. In the training day, at first, blood samples were obtained at 07:30 AM in fasting state. Then, subjects performed training protocol for 50 min duration that included 15 min warm-up, 25 min main activity, and 10 min cool-down, and after three min, subsequent blood samples were obtained. To measure serum levels of glucose, cholesterol, the Brain-Derived Neutrophilic Factor (BDNF) enzymatic and ELISA methods were used, respectively. To analyze the obtained data, paired-samples t test and Pearson correlation were used, and statistical significance was set at P<0.05.  Results Results showed that serum concentration of BDNF (P=0.002) and glucose (P=0.01) increased significantly. Also, there were no significant correlations between serum concentration of BDNF and glucose in both pretest and posttest (P>0.05). However, there were near significant negative correlation between serum concentration of BDNF and cholesterol in pretest (r=-0.53, P=0.061) and significant negative correlation in posttest (r=-0.703, P=0.007). Conclusion Early morning exercise for approximately 50 minutes increases serum concentration of BDNF and glucose in elderly males. Also, there is no significant positive correlation between them. But, there is significant negative correlation between serum concentration of BDNF and cholesterol. Therefore, early morning exercise for the elderly men is recommended to improve brain health. Also, older men, if they have normal cholesterol levels, will get more benefits from early morning exercise.